SoC with an integrated DSP and a 2.4-GHz RF transmitter. - Staszewski, R.B (IEEE Transactions on VLSI systems)
We present a system-on-chip (SoC) that integrates a TMS320C54x digital signal processor (DSP), which is commonly used in cellular phones, with a multigigahertz digital RF transmitter that meets the Bluetooth specifications. The RF transmitter is tightly coupled with the DSP and is directly mapped to its address space. The transmitter architecture is based on an all-digital phase-locked loop (ADPLL), which is built from the ground up using digital techniques and digital creation flow that exploit high speed and high density of a deep-submicrometer CMOS process while avoiding its weaker handling of voltage. The frequency synthesizer features a wideband frequency modulation capability. As part of the digital flow, the digitally controlled oscillator (DCO) and a class-E power-amplifier are created as ASIC cells with digital I/Os. All digital blocks, including the 2.4-GHz logic, are synthesized from VHDL and auto routed. The use of VHDL allows for a tight and seamless integration of RF with the DSP. To take advantage of the direct DSP-RF coupling and to demonstrate a software-defined radio (SDR) capability, a DSP program is written to perform modulation of the GSM standard. The chip is fabricated in a baseline 130-nm CMOS process with no analog extensions and features high logic gate density of 150 kgates per mm2. The RF transmitter area occupies only 0.54 mm2, and the current consumption (including the companion DSP) is 49 mA at 1.5-V supply and 4 mW of RF output. This proves attractiveness and competitiveness of the "digital RF" approach, whose goal is to replace RF functions with high-speed digital logic gates.